Understanding Conversational Interruptions in Thai News Interview Programmes: An Analysis of Functions and Participant Objectives - Nuengruthai Pankaew; Supakit Buakaw (Acta Universitatis Sapientiae: Philologica)
. The Thai news interview programme serves as a platform where two parties of interviewees with differing opinions on a specific topic are invited for an interview It is common for conversations in these programmes to be interrupted by the interlocutor The objective of this article is to examine the functions of conversational interruptions in Thai news interview programmes The data for the study were collected from 25 episodes of Thai news interviews, and the verbal content from these programmes was transcribed into written language To analyse the conversational data, the researcher employed the conversational analysis framework on the turntaking and the framework of conversational interruptions. The findings of the study revealed that listeners produced a total of 2,677 conversational interruptions These interruptions were categorized into three main functions: intrusive interruption, cooperative interruption, and neutral interruption It was observed that interviewers attempted to interrupt in order to successfully manage the interview, while interviewees interrupted to provide additional information and assert their right to speak They also interrupted each other to gain the opportunity to speak and express disagreement Therefore, it can be concluded that all parties involved in the conversations used interruption as a means to demonstrate their roles and defend their right to speak.